Kontribusi Tenaga Kerja Perempuan Pada Usahatani Jahe Merah Di Desa Mokobang Kecamatan Modoinding Kabupaten Minahasa Selatan - Maleke, Reginal Francois; Waney, Nordy Fritsgerald Lucky; Wariki, Barce A.F. (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the contribution of female labor to ginger farming in Mokobang Village, Modoinding Sub-district, South Minahasa Regency. The research was conducted for three months from May to July 2023. The location was determined purposively, the research was conducted in Mokobang Village, Modoinding Sub-district, South Minahasa Regency. The data used in this research are primary and secondary data. Primary data was obtained from direct interviews with farmers using a list of questions that had been prepared. Secondary data were obtained from relevant agencies, as well as other literature related to the research. The method used in sampling is by purposive sampling. Intentional sampling or purposive sampling based on criteria. Some of the farmer criteria taken such as red ginger farmers in Mokobang Village who employ female labor. The number of samples in this study was 15 respondents from a population of 105 farmers. The data analysis method used in this research is descriptive analysis. The contribution of female labor to red ginger farming in Mokobang Village is 51.98%. The contribution of female labor in red ginger farming is greater than male labor.